Innovative approach in the improvement of student’s attention - Kauliņa, Anda; Voita, Daina; Porozovs, Juris; Vaļēviča, Evita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Integrated studies are aimed towards linking knowledge from a variety of subjects. By studying related subjects in an isolated manner the knowledge is acquired in a disorganized way. Therefore contemporary pedagogy demands the use of integrative teaching methodology to achieve the best results. An Integrative teaching methodology for children with learning difficulties and cognitive and motor disorders was used in 17 schools from different Latvian regions. Students acquired Integrative teaching methodology during one study year. Attention span and concentration abilities using Cognitron test from Vienna test system were estimated for 615 students before and after the acquiring of Integrative teaching methodology. The results of younger students have improved more than the results of older students after using this methodology. The largest increase of speed and accuracy of information processing was observed for 3-4 grade students of general schools.